PHYTOMASS OF THE CROWNS COMPONENTS OF PINUS SYLVESTRIS L. TREES WITHIN NORTHERN STEPPE OF UKRAINE - Lakyda, P. I.; Lovynska, V. M. (Forestry and Forest Melioration, 2018)
Introduction The components of the crown phytomass play a key role in the plants life as they synthesize organic substances and take part in the gas interchange processes CO2 deposition and production of O2. Scots pine (Pinus sylvestris L.) is the main coniferous forest-forming species within the Northern Steppe of Ukraine. The aim of the study was to develop the regulatory reference which can be applied to estimate the phytomass of the crown components of Scots pine trees within the Northern Steppe of Ukraine. Materials and Methods To investigate the aboveground components of the crown phytomass we used the data obtained on 20 temporary sample plots within the territory of Dnipropetrovsk Region. We also assessed the crown phytomass fraction of a tree by means of the Lakyda method (2002). In addition, the working mass data of biometric indicators for the sample trees were formed. It included age, diameter at breast height, tree height, the mass of tree greenery, the mass of branches, needle mass and relative density of stands. To calculate the phytomass of the crown components, we applied regression equations. Results In this article, we provide the results of the basic statistics calculation for the crown phytomass components for sample pine trees. The correlation analysis showed that there was a direct relationship between all crown components and all biometric indexes. We found out that the strongest relationship was between the mass of tree greenery, branches, and needles with a diameter at breast height. Furthermore, we provide the equation of dependence of the crown phytomass fractions on the tree diameter and height, as well as on the crown diameter and length, the tree age and relative stand density. We discovered that a connection of crown components with different influencing factors can be described by the allometric regression equations with R2 from 0.41 to 0.80. Higher determination coefficients are noted for the equations used to calculate the phytomass of tree greenery and needles, whereas for branches phytomass they are less significant. All calculated mathematical models had a negative coefficient for the tree height which confirms the decrease in the concentration of phytomass of assimilating organs with the aging of stands. Accordingly, there was a negative correlation between the crown components phytomass accumulation and the height of the stand. We calculated and provided in the article the fragment of standards to estimate the phytomass crown components for Scots pine trees. Thus, the phytomass of tree greenery, branches and needles grew with an increase of diameter at breast height. At the same time, we found out that the higher the trees of the same diameter, the less their analyzed parameters are. We also revealed the results of calculating the crown phytomass of pine trees in an absolutely dry state. A comparative analysis of the obtained results on the phytomass of pine tree greenery and branches with the data obtained for this species in Polissya, Forest-Steppe of Ukraine, Russia, and Kazakhstan was carried out. Conclusions The developed regulatory reference describes the components of crowns phytomass of Scots pine trees in detail. We concluded that it can be used to estimate the products of the species’ crown components within the Northern Steppe of Ukraine. 1 Fig., 8 Tables, 16 Refs.